A novel phylogeny for the genus Echinococcus, based on nuclear data, challenges relationships based on mitochondrial evidence - Saarma, U.; Jogisalu, I.; Moks, E.; Varcasia, A.; Lavikainen, A.; Oksanen, A.; Maravilla, P. (Cambridge Univ Press, 2009)
The taxonomic status of Echinococcus, an important zoonotic cestode genus, has remained controversial, despite numerous attempts to revise it. Although mitochondrial DNA (mtDNA) has been the source of markers of choice for reconstructing the phylogeny of the genus, results derived from mtDNA have led to significant inconsistencies with earlier species classsifications based on phenotypic analysis. Here, we used nuclear DNA markers to test the phylogenic relationships of members of the genus Echinococcus. The analysis of sequence data for 5 nuclear genes revealed a significantly different phylogeny for Echinococcus from that proposed on the basis of mitochondrial DNA sequence data, but was in agreement with earlier species classifications. The most notable results from the nuclear phylogeny were (1) E. multilocularis was placed as basal taxon, (2) all genotypes of Echinococcus granulosus grouped as a monophyletic entity, and (3) genotypes G8 and G10 Clustered together. We conclude that the analysis Of nuclear DNA data provides a more reliable means of inferring phylogenetic relationships within Echinococcus than mtDNA and suggest that mtDNA should not he used as the sole soul-cc of markers in future studies where the goal is to reconstruct a phylogeny that does not only reflect a maternal lineage, but aims to describe the evolutionary history at species level or higher.
Keywords: Echinococcus; nuclear genes; mitochondrial genes; phylogeny